The Influence of Self-Efficacy and Attitude Towards Digital Technologies on Teachers’ Technology, Pedagogy and Content Knowledge - Asrofi (Curtin University, 2023)
This research aims to investigate Indonesian teachers’ perceptions of self-efficacy and attitudes towards digital technologies, as well as their technological, pedagogical, and content knowledge (TPACK) in teaching and factors that affect digital technology integration into classroom. A mixed-methods approach was employed. Finding revealed that teachers ‘possessed good self-efficacy, attitudes, and TPACK in the classroom. Findings also suggested that students’ access to ICT facilities was the most preventive factor for employing digital tools in the classroom.